Shear Strength of Adhesively bonded Joints with Toughened Mussel Shell Powder - Velayutham, Subashini; Sugiman, Sugiman; Ahmad, Mohd Hilton; Mohd Jaini, Zainorizuan (International Journal of Integrated Engineering, 2024)
Mussel shell is a household wastes usually disposed into landfills, causing environmental pollutions, disease-borne and unpleasant smell. Mussel shell particulates can be incorporated as filler to enhance shear strength in epoxy resin due to its high calcium carbonate content. Formerly synthetic fillers were used to improve the shear strength of epoxy resin, but dependency on mineral-derived substances may increase green-house effect. It was found that mechanical properties of neat epoxy resin can be enhanced by adding calcium carbonate particles. In this paper, the physical properties and shear strength of epoxy toughened with mussel shell powder (TEMP) were investigated. Single lap joint (SLJ) specimens were tested for shear strength with incorporation of various TEMP volume fractions and over-lap length. Collected dried mussel shell were crushed, grinded and later sieved to pass 75 µm size prior to mixing with Epikote 828 epoxy resin, with epoxy to hardener volume ratio of 5:2. The testing series includes TEMP volume fractions between 0% to 10% (by 2.5% increment) and overlap length ranging 12.7 – 50.8 mm. The results demonstrated that the longest overlap length and 7.5% TEMP volume fractions exhibited a significant effect to the ultimate joint strength. From SEM microscope, 10% TEMP was prone to particle agglomerations and gave less joint strength. The joint strength with 7.5% mussel shell powder was stronger compared with other volume fractions, with the strength enhancement of 169.6%.